Giant left atrium. Issue 2 (March 1970) - Le Roux, B. T.; Gotsman, M. S.
Abstract : Radiographic evidence of asymmetrical enlargement of the left atrium without atrial infarction is presented. Giant atrial enlargement is rarely symmetrical, the atrial appendage can contribute to the enlargement, and the giant atrium can be effectively trimmed. This will reduce its size and, therefore, the space which it occupies, and will restore the anatomical relations of neighbouring structures such as the main bronchi.